Os conflitos homofóbicos na escola e a teoria do reconhecimento - Dani, Grasiela Cristine Celich (2011)
The present dissertation talks about Homophobic conflict in school, and the theory of recognition . It belongs to the research line Scholastic Practices and Public Policies of the Post-Degree Program in Education of the Universidade Federal de Santa Maria, Rio Grande do Sul. Such dissertation has as a goal to discuss in which way the theory of recognition can contribute for the understanding and solution of homophobic conflicts in school, among High School students. In order to achieve such thematic propose it was chosen the interactive method, founded on the dialectic-hermeneutical process. As a research tool, it is used the application of a questionnaire to collect the opinion of High School students concerning homoaffection, prejudice, homophobia, as well as the recognition of the homosexuals, with the intention of solving the homophobic conflicts. It s important to mention that the results of the research are evaluated taking in consideration a qualitative and quantitative approach. In the data analyses, it is possible to ascertain how the homophobia is formed. Based on that, it is shown ways of how the scholastic homophobic conflict can be worked and confronted, with the intention of comprehending and solving it. Thus, it is possible to conclude the dissertation with a positive response when it comes to the attempt of solving homophobic conflicts in school. Such attempt is possible through the theory of recognition of Hegel (2008) and Honneth (2009).